Implikasi Kebijakan Persaingan Usaha Produk Usaha Mikro Kecil Menengah (UMKM) Untuk Meningkatkan Perekonomian di Kabupaten Serang - Sulasno, Sulasno; dwisvimiar, Inge (SKeTsa Bisnis (e-jurnal), 2022)
English Version Small and medium enterprises are one of the breakthroughs in increasing economic growth in the midst of society to achieve adequate welfare. MSME activities train people to have high skills, creativity, and productivity so that they are expected to be able to compete. The existence of business competition requires the Indonesian people to improve their business strategies so that they can compete with other products. This research uses qualitative research (empirical juridical) which is legal research regarding the enforcement or implementation of normative legal provisions in action on every particular legal event that occurs in society. The purpose of this study is to determine the strategy and application of legal protection against business competition products of micro, small and medium enterprises (MSMEs) in Serang Regency and to know the development of legal protection against business competition products of micro, small and medium enterprises (MSMEs) in Serang Regency. The existence of business competition requires the community to improve business strategies so that they are able to compete with other products. One form of legal protection for MSME products is in the form of Intellectual Property Registration (KI). The government assists SMEs in registering IP rights, namely trademark rights and copyrights Indo Version Penelitian ini menggunakan penelitian kualitatif (yuridis empiris) adalah penelitian hukum mengenai pemberlakuan atau implementasi ketentuan hukum normatif secara in action pada setiap peristiwa hukum tertentu yang terjadi dalam masyarakat. Tujuan penelitian ini yaitu mengetahui, meemahami, dan menganalisa strategi dan penerapan perlindungan hukum terhadap persaingan usaha produk usaha mikro kecil menengah (UMKM) di Kabupaten Serang dan pengembangan perlindungan hukum terhadap persaingan usaha produk usaha mikro kecil menengah (UMKM) di Kabupaten Serang. Dengan adanya persaingan usaha menuntut masyarakat untuk meningkatkan strategi usaha sehingga mampu bersaing dengan produk-produk lainnya. Pemerintah berupaya dan mendorong terwujudnya para pelaku UMKM dalam melindungi produk-produknya melalui proses permohonan pendaftaran Kekayaan Intelektual (KI) yaitu hak merek maupun hak Cipta. Sementara itu para pelaku UMKM belum mempunyai komitmen yang bisa dipertanggungjawabkan.